Antonim Mutlak dalam Bahasa Jawa: Kajian Semantik Leksikal - Endang Sri Maruti; Bambang Eko Hari Cahyono (Universitas Mulawarman, 2021)
The purpose of this study is to describe and classify absolute antonyms in Javanese. This research is a descriptive qualitative type. The data are in the form of words, phrases, clauses, and sentences containing absolute antonyms taken from Javanese textbooks and textbooks in elementary and high schools. Data collection techniques with documentation, listening, and record. The data were analyzed using the